2022
DOI: 10.34067/kid.0005522022
|View full text |Cite
|
Sign up to set email alerts
|

Point of Care Ultrasound in Cirrhosis-Associated Acute Kidney Injury: Beyond Inferior Vena Cava

Abstract: This is an Early Access article. Please select the PDF button, above, to view it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…[45] The use of POCUS in classifying the type of AKI in cirrhosis is an important evolving domain in HRS-AKI management. [46] A recent study on pulmonary artery catheterization in cirrhosis-AKI showed that 62% of patients diagnosed with HRS by clinical criteria have elevated pulmonary capillary wedged pressure and were counterintuitively started on diuretics. [47] Patients can be better assessed for volume resuscitation in AKI using IVC dynamics, [48] and incorporation of POCUS is recommended in an updated HRS-AKI management algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…[45] The use of POCUS in classifying the type of AKI in cirrhosis is an important evolving domain in HRS-AKI management. [46] A recent study on pulmonary artery catheterization in cirrhosis-AKI showed that 62% of patients diagnosed with HRS by clinical criteria have elevated pulmonary capillary wedged pressure and were counterintuitively started on diuretics. [47] Patients can be better assessed for volume resuscitation in AKI using IVC dynamics, [48] and incorporation of POCUS is recommended in an updated HRS-AKI management algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to incorrect interpretation during follow-up studies, particularly when different operators are performing the study. Therefore, the IVC must be examined in both long and short axis views, where feasible[ 27 , 28 ]. Also, in conditions such as cirrhosis, IVC size/shape may be altered by the local structural changes, making it unreliable to predict RAP.…”
Section: Point-of-care Ultrasoundmentioning
confidence: 99%
“…The term extended venous excess ultrasound score (E-VExUS) or extended VExUS has been proposed to include Doppler interrogation of additional veins such as the internal jugular, superior vena cava, splenic, and femoral veins in situations where the primary veins ( e.g. , hepatic, portal in cirrhosis, and intrarenal in advanced kidney disease) suffer from limitations[ 28 , 48 ]. This also includes estimation of RAP by greyscale POCUS of the internal jugular vein where IVC is not accessible or unreliable.…”
Section: Point-of-care Ultrasoundmentioning
confidence: 99%
“…37 Unfortunately, IVC size is not a reliable indicator of cardiac output may not be indicative of the patient's true volume status or fluid responsiveness. 38 For example, in a small, observational study of patients with acute liver failure and shock, IVC distensibility was a poor predictor of fluid responsiveness. 25 IVC indices are better indicators of fluid tolerance, meaning that if the clinical situation calls for fluid resuscitation and the IVC is collapsing, then the patient will likely be able to tolerate fluids.…”
Section: Ivc Diameter and Collapsibilitymentioning
confidence: 99%
“…Unfortunately, IVC size is not a reliable indicator of cardiac output may not be indicative of the patient's true volume status or fluid responsiveness 38 . For example, in a small, observational study of patients with acute liver failure and shock, IVC distensibility was a poor predictor of fluid responsiveness 25 .…”
Section: The Need For Precise Volume Assessment In Cirrhosismentioning
confidence: 99%